CeO2 nanoparticles and cerium species as antiviral agents: Critical review - Alexander B. Shcherbakov (Elsevier, 2024)
Viral infections account for a large proportion of the total number of fatal diseases and require close attention from the international public health community. The COVID-19 pandemic has highlighted problems in medicine and healthcare related to the search for effective substances for the prevention, diagnosis and treatment of viral infections. According to many scientific studies, cerium species are very promising biomedical materials for combatting viral infections and have shown encouraging results in killing viruses on non-living objects, reducing viral load both in vitro and in vivo, relieving symptoms and reducing the consequences of viral diseases. This review critically examines the current level of knowledge on cerium species and their practical applications, with a focus on CeO2 nanoparticles (CeNPs). This review also seeks to assess the prospects for their development and use in antiviral theranostics.